Patient Selection for Follicular Unit Extraction versus Linear Strip Donor Harvesting - Konior, Raymond J. (Facial Plastic Surgery, 2023)
Follicular unit grafts can be harvested using two methods: strip follicular unit transplantation and follicular unit excision. Each method can generate outstanding results, but both are uniquely different with respect to the advantages and disadvantages they offer. Devising a sound surgical plan is instrumental to assure that a patient's short-term and long-term goals can be met, but creating the best plan possible for the graft harvest process is not straightforward. This paper will review the various advantages and disadvantages of each graft harvest method, along with their short-term and long-term ramifications, so as to provide insight into the process by which a sound surgical plan can be developed for any patient seeking surgical hair restoration.
Keywords: linear strip excision (LSE); follicular unit excision (FUE); surgical plan; safe donor area (SDA); donor scarring; graft yield